2021
DOI: 10.5271/sjweh.3961
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of employer characteristics to continued employment of employees with residual work capacity: evidence from register data in The Netherlands

Abstract: The contribution of employer characteristics to continued employment of employees with residual work capacity: evidence from register data in The Netherlands by van Ooijen R, Koning PWC, Boot CRL, Brouwer S This paper assesses the contribution of employer characteristics to continued employment of employees with residual work capacity using register data. We found sizable differences in employment outcomes between similar employers in terms of size, sector and workforce-composition, implying that encouraging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
2
16
2
Order By: Relevance
“…For employer size, the evidence is inconsistent (Jansen et al, 2021). Some studies found that working for a large employer is positively associated with RTW, retention, or continued employment (Hannerz et al, 2012;Prang et al, 2016;Schneider et al, 2016;van Ooijen et al, 2021); others found that working for a smaller employer is positively associated with early RTW or continued employment, or that small workplaces had lower entry into certified absence (Faucett et al, 2000;Krause et al, 2001;Holm et al, 2007;Markussen et al, 2011); or no association was found at all (Cooper et al, 2013;Høgelund and Holm, 2014;Bacon and Hoque, 2022). The inconsistent evidence can probably be partially explained by different definitions of employer sizes between studies, as definitions can vary according to national standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For employer size, the evidence is inconsistent (Jansen et al, 2021). Some studies found that working for a large employer is positively associated with RTW, retention, or continued employment (Hannerz et al, 2012;Prang et al, 2016;Schneider et al, 2016;van Ooijen et al, 2021); others found that working for a smaller employer is positively associated with early RTW or continued employment, or that small workplaces had lower entry into certified absence (Faucett et al, 2000;Krause et al, 2001;Holm et al, 2007;Markussen et al, 2011); or no association was found at all (Cooper et al, 2013;Høgelund and Holm, 2014;Bacon and Hoque, 2022). The inconsistent evidence can probably be partially explained by different definitions of employer sizes between studies, as definitions can vary according to national standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…that organizations have policies on training and development, or supporting technologies to facilitate learning [33]. Moreover, from this study, it is not clear whether the size of the company or type of workplaces influences the guidance of supervisors, while research shows that this could have an effect on employment [34]. Studies that examined the differences between supported and sheltered workplaces showed that employees in supported workplaces are more satisfied with their job than employees in sheltered workplaces [17].…”
Section: Implications For Research and Practicementioning
confidence: 84%
“…Management of work disability is a universal problem,1 2 while premature termination of careers due to work disability is one of the major socioeconomic challenges globally 3. However, the solutions and the activity to manage work disability may differ across countries 1 2 4. Generally, the emphasis of occupational healthcare (OHC) is to promote healthy workplaces and prevent accidents and hazards in workplaces,5 but the ageing of the workforce also calls for active preventive interventions of OHC units 6…”
Section: Introductionmentioning
confidence: 99%
“…This means an active collaboration between the workplace and OHC unit in the work ability management process 23 24. Employers’ (supervisors’) level of activity in work ability management differs, being lowest in small enterprises and low-wage service-oriented sectors 4. Supervisors’ activity and skills affect work-related sickness absence and disability retirement incidence 25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation